Accumulation of phenolic compounds in the fruit of new introduced varieties of (Lonicera edulis Turcz. ex Freyn) in the conditions of Belarus - Rupasova, Zhanna; Dobryanskaya, Ksenia; Sulim, Daria; Zadalia, Viktoriya; Pavlovsky, Nikolai; Pavlovskaya, Alla; hatravko, Valentin; Belyi, Pavel; Goncharova, Lyudmila; hpitalnaya, Tamara (Journal of the Belarusian State University. Ecology, 2023)
The results of a comparative study in the southern agroclimatic zone of Belarus in the contrasting hydrothermal regime seasons of 2021 and 2022 are presented. parameters of accumulation of the main groups of bioflavonoids and tannins in the fruits of 5 new introduced varieties of edible honeysuckle – Aurora, Honeybee, Indigo Gem, Wojtek, Zojka and the zoned variety Leningradsky giant, chosen as a comparison standard. It was established that the reduced and very uneven temperature background of the second season during the period of fruit formation contributed to their preferential enrichment in comparison with the previous, warmer season by 8–50 % in anthocyanins proper and by 13–43 % in tannins, the most significant in the first case in varieties Honey bee, in the second – in varieties Leningradsky giant and Indigo gem, against the background of a predominant depletion of 14–38 % in leukoanthocyanins and to a lesser extent (by 6–14 %) in catechins in the absence of significant interseasonal differences in the accumulation of flavonols and in most cases in overall output of P-vitamins. In most honeysuckle taxa, especially in the Honey bee variety, a positive effect of an unfavorable temperature background on the totality of the characteristics of the phenolic complex of fruits and a negative one in the Indigo gem variety were found, with the most pronounced resistance to this factor in the Wojtek variety.
Keywords: weather conditions; edible honeysuckle; varieties; fruits; tannins; bioflavonoids; antoсian pigments; catechins; flavonols